Three-dimensional stereophotogrammetric evaluation of facial soft tissue asymmetries before and after orthognathic surgery in skeletal class III patients - Logothetis, Georgios (My University, 2020)
Amaç: Bu çalışmanın amacı, Sınıf III ortognatik cerrahi öncesi ve sonrası, yüz bölgesindeki yumuşak doku asimetrilerinin steryofotogrametri ile incelenmesidir.Gereç ve Yöntem: Retrospektif çalışma örneklemini; ortalama yaşları 20.44 olan (17-27 arasında değişen) 40 iskelet Sınıf III hastanın (19 erkek, 21 kadın), üç boyutlu (3B) yüz görüntüleri oluşturmaktadır. 3B yüz görüntüleri T0 (ameliyattan önce) ve T1 (ameliyattan 6 ay sonra) zaman aralıklarında alınmış ve Etkileşimli En Yakın Nokta (ICP) algoritması kullanılarak ayna görüntüsü alınmış versiyonları ile çakıştırılmıştır. Sonrasında bir orta oksal düzlem (MSP) yaratılmış, yüz 5 parçaya (üst, orta, alt yüz, maksiller ve mandibuler) bölünmüş ve sistem tarafından otomatik olarak, yüzün ve yüz parçaların asimetri seviyelerini gösteren Kök Ortalama Kare (RMS) değeri elde edilmiştir. Bulgular: Tüm yüz ve her parça için, iki zaman aralığı arasında RMS değerlerinde anlamlı olmayan bir düşüş gözlendi (P>0,05). İlk asimetri düzeyleri ile ameliyat sonrası asimetri düzeyleri arasında istatistiksel olarak anlamlı bir korelasyon bulundu (r=0.653, P<0.01). Bu bulguların daha fazla detaylandırılması amacıyla örneklem, her biri 20 hastadan oluşan Düşük ve Yüksek RMS değerlerine sahip iki alt gruba ayrıldı. Düşük RMS grubu için asimetri seviyelerinde istatistiksel olarak anlamlı bir artış bulundu (P<0.05). Sonuç: Başlangıç asimetri değeri yüksek olan hastalar ameliyat sonrası artmış simetri değeri göstermektedir.

Aim: To investigate the asymmetry levels of the facial surface before and after the Class III orthognathic surgery procedure with the use of stereophotogrammetry.Materials and Methods: The sample of this retrospective study consists of three-dimensinal (3D) facial images of 40 skeletal Class III orthognathic surgical patients (19 males, 21 females), mean age 20,44 years (ranging from 17 to 27 years old). The 3D images acquisition took place at the T0 (before surgery) and T1 (6 months after surgery) time intervals. The 3D models were cropped, mirrored and the original and mirrored version were registered together. A mid-sagittal plane (MSP) was created and a Root Mean Square (RMS) value was automatically calculated by the system. The face was divided into parts (upper, mid, lower face subdivided to maxillary and mandibular region). Finally, volumetric and surface analyses were performed.Results: A non-significant decrease in RMS values was observed between the two time intervals (P>0,05). A statistically significant correlation was found between the initial asymmetry levels and the amount of asymmetry correction after surgery (r=0.653, P<0.01). The sample was separated into two subgroups, of 20 patients each, of Low and High RMS values. A statistically significant increase in the asymmetry levels was found for the Low RMS group (P<0.05) and a significant decrease in asymmetry was found for the High RMS group for the whole facial surface (P<0.01) and for the lower and specifically the mandibular facial parts (P<0.05). A significant correlation between the change in RMS values and the changes in angulation of the MSP plane was observed (r=-0.392, P<0.05). Conclusion: Patients showing increased initial symmetry levels end up more asymmetric after surgery and patients with higher values of initial asymmetry show bigger improvement in their symmetry levels.
Keywords: Asimetri; Class III; Dentistry; Diş hekimliği; Orthognathic surgery; Ortognatik cerahi; Sınıf III; Stereophotogrammetry; Steryofotogrametri; Three-dimensional imaging; Üç boyutlu görüntülem Asymmetry